2008
DOI: 10.1097/01.ccm.0b013e3181611f62f
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G treatment of postcardiac surgery patients with score-identified severe systemic inflammatory response syndrome—The ESSICS study*

Abstract: Patients undergoing cardiac surgery (involving cardiopulmonary bypass) who develop severe SIRS derive no improvement in short-term morbidity or 28-day mortality from ivIgG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Preoperative intravenous methylprednisolone (10 mg/kg) caused a reduction in the serum concentrations of many of these cytokines after CPB, but this reduction was not associated with improved hemodynamic variables, diminished blood loss, less use of inotropic agents, shorter duration of ventilation, or shorter ICU length of stay (63). Similarly, the use of intravenous immunoglobulin G in patients with post-CPB SIRS has not been associated with decreased rates of short-term morbidity or 28-day mortality (64).…”
Section: Use Of Cpbmentioning
confidence: 97%
“…Preoperative intravenous methylprednisolone (10 mg/kg) caused a reduction in the serum concentrations of many of these cytokines after CPB, but this reduction was not associated with improved hemodynamic variables, diminished blood loss, less use of inotropic agents, shorter duration of ventilation, or shorter ICU length of stay (63). Similarly, the use of intravenous immunoglobulin G in patients with post-CPB SIRS has not been associated with decreased rates of short-term morbidity or 28-day mortality (64).…”
Section: Use Of Cpbmentioning
confidence: 97%
“…For example, a pilot study found that the use of intravenous immune globulin (IVIG) following cardiac surgery in high‐risk patients significantly improved the Acute Physiology and Chronic Health Evaluation (APACHE) II scores, 8 a measure of overall disease severity in critically ill patients and a surrogate endpoint for mortality 9 . However, when the larger follow‐up RCT was completed, there was no difference in the 28‐day mortality in patients treated with IVIG 10 . In this case, the surrogate measure was not a good indicator of clinically relevant treatment effects.…”
Section: When Is a Surrogate Endpoint Useful?mentioning
confidence: 99%
“…It is also important to consider serial scoring, which looks at the effectiveness of therapies and the trend during hospitali zation [42,43]. This aspect and the ana lysis of scorespecific subscores, especially the question on the role of inflammation and organ dysfunction, are very interest ing, and we are currently analyzing these data to publish them soon.…”
Section: Scoring In Cardiogenic Shockmentioning
confidence: 99%
“…Identification of these patients in the ICU is clinically important [34]. Previous studies of patients with MODS or sepsis have shown the rele vance of several scoring systems such as the APACHE II [22,42,43] Originalien culation is more complex and laborious. However, a scoring system is only valid for a special group of patients when it has been validated on this group.…”
mentioning
confidence: 99%
See 1 more Smart Citation